Relationship between elevated serum direct bilirubin and atrial fibrillation risk among patients with coronary artery disease - Yanbin Song; Yanbin Song; Wenhua Li; Wenhua Li (Frontiers in Medicine)
BackgroundObservational studies have shown that the direct bilirubin (DBIL) is correlated with metabolic syndrome and cardiovascular disease. However, it remains unclear whether DBIL is associated with atrial fibrillation (AF) risk in the patients with coronary artery disease (CAD). This study aimed to investigate the association between serum DBIL levels and AF in CAD patients.MethodsA total of 937 patients diagnosed with CAD were retrospectively included. Serum total bilirubin (TBIL), DBIL, lipid profiles, and other data were collected and analyzed between the AF and non-AF groups. The characteristics of participants were compared based on their DBIL tertiles. Univariate and multivariate logistic regression models, as well as restricted cubic spline (RCS) regression, were used to explore the relationship between DBIL and AF.ResultsAF was observed in 72 (7.7%) patients. There was a significant higher level of DBIL in the AF patients compared to non-AF patients (p < 0.001). Individuals from the DBIL T3 group, when compared to those from the T1 or T2 groups, were more likely to have a higher proportion of AF and lower levels of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (Apo B) and triglyceride-glucose (TyG) (all p < 0.001). Univariate logistic regression showed that the OR for AF in patients in T3 was 2.796 (95% CI, 1.528–5.116, p = 0.001) compared with participants in T1. The result remained consistent in the multivariate logistic regression (T3 versus 1: adjusted OR: 2.239). The RCS curve demonstrated a significant nonlinear association between DBIL and AF. Subgroup analysis revealed that this association was significant among patients aged ≥65 years old, with body mass index (BMI) < 25, and with diabetes mellitus (DM).ConclusionThe study suggested a robust relationship between higher levels of DBIL and an increased risk of AF in CAD patients. The association of elevated DBIL with the incidence of AF was higher in CAD patients older than 65 years, with a BMI < 25, and those with DM.